Psychosocial correlates of HPV vaccine acceptability in college males: A cross-sectional exploratory study - Ovidiu Tatar; Samara Perez; Anila Naz; Gilla K. Shapiro; Zeev Rosberger (Papillomavirus Research, 2017)
Background: Most college males are not immunized against the human papillomavirus (HPV) and are at high risk of HPV infection. Most research of correlates of HPV vaccine acceptability in college males has assessed vaccine acceptability as a binary outcome, e.g., vaccinated or not vaccinated, without considering that some students may not even be aware that the HPV vaccine can be given to males. Our objective was to evaluate the psychosocial correlates of HPV acceptability in college males, based on multiple stages of HPV decision-making. Methods: We used an online questionnaire to collect data from college men aged 18â26 enrolled at three Canadian universities between September 2013 and April 2014. Vaccine acceptability assessment was informed by the six-stage decision-making Precaution Adoption Process Model (PAPM). We sought information on socio-demographics, health behaviors, HPV vaccine benefits and barriers, worry, susceptibility, severity related to HPV infection and social norms. HPV and HPV vaccine knowledge was measured with validated scales. Psychosocial correlates of HPV vaccine acceptability were assessed with bivariate and multivariate multinomial logistic regression. Actual and perceived HPV and HPV vaccine knowledge scores were calculated. Results: The final sample size was 428. Most male college students were unaware that the HPV vaccine could be given to males, unengaged or undecided about getting the HPV vaccine. Significant correlates of higher HPV vaccine acceptability were: increased HPV knowledge, having discussed the HPV vaccine with a healthcare provider, and social norms. Being in an exclusive sexual relationship was significantly associated with lower HPV vaccine acceptability. Students' actual HPV and HPV vaccine knowledge was low and positively correlated to their perception about their HPV knowledge. Conclusions: We provided a fine-tuned analysis of psychosocial correlates of HPV vaccine acceptability in college males who are in the early stages of HPV vaccine decision-making. Interventions are needed to increase HPV and HPV vaccine knowledge in college males. Keywords: Human papillomavirus, Vaccine, Acceptability, Psychosocial correlates, College men